Epistemology of Islamic Education in the Qur'an: Themes, Methods, and Pedagogical Implications - Suhardi Suhardi; Sutrisno Sutrisno; Saiful Ahyar (AL-ISHLAH: Jurnal Pendidikan, 2026)
Education in Islam is fundamentally rooted in the Qur’an, which provides comprehensive guidance on knowledge, learning, and human development. However, studies on Islamic educational epistemology often remain fragmented and lack systematic thematic synthesis. This study employs a qualitative literature-based approach using thematic content analysis of selected Qur’anic verses related to education. Primary data were derived from the Qur’an, while secondary sources included classical and contemporary tafsir and scholarly works on Islamic education. Verses were purposively selected based on their relevance to key educational themes and analyzed through coding, categorization, and interpretative synthesis. Source triangulation was applied to enhance analytical rigor. The findings reveal that the Qur’an constructs a holistic epistemological framework of education encompassing (1) the obligation of seeking and transmitting knowledge, (2) educational goals oriented toward spiritual, moral, and social development, (3) diverse pedagogical methods such as wisdom, dialogue, and ethical instruction, and (4) integrated concepts of educators and learners grounded in responsibility, character, and intellectual engagement. Additionally, educational content is centered on monotheism, morality, and social responsibility, while evaluation emphasizes moral accountability. These findings indicate that Islamic educational epistemology integrates revelation, reason, and experience into a unified system that promotes holistic human development. The study contributes to bridging classical Qur’anic insights with contemporary educational discourse, although its reliance on textual analysis limits empirical applicability. Future research should explore the operationalization of these principles in modern educational contexts.